THE SIGNIFICANCE OF THE LEVEL OF AVERAGE WEIGHT MOLECULES IN BLOOD PLASMA, AS AN INDICATOR OF ENDOGENOUS INTOXICATION, IN PREDICTING GLOMERULONEPHRITISIS IN CHILDREN WITH HEMORRHAGIC VASCULITIS - Пшеничная, Елена Владимировна; Астафьева, Елена Васильевна (Mother and Baby in Kuzbass, 2024)
Purpose of the study – to assess the level of molecules of average mass in blood plasma, as an indicator of endogenous intoxication, as a predictor of the development of glomerulonephritis in children with hemorrhagic vasculitis. Material and methods. 74 children with hemorrhagic vasculitis were examined. Patients are divided into 3 groups. Group I included 53 patients with the abdominal form, group II included 21 patients with the articular form of vasculitis. Group III was formed retrospectively in the amount of 21 patients from patients in group I, when they developed clinical and laboratory signs of glomerulonephritis at 3-5 weeks from the onset of the disease. The content of molecules of average mass was determined by direct spectrometry of the deproteinized supernatant after precipitation of proteins with a solution of trichloroacetic acid at a wavelength of 254 nm. The control group consisted of 23 healthy peers. Results. The main deviations in the indicator of molecules of average mass, indicating the level of endogenous intoxication, were noted in children with the abdominal form of vasculitis and, especially, in patients with developed glomerulonephritis. A higher level of endogenous intoxication correlated with the severity of the patients’ condition. The indicators of average mass molecules established in such cases were statistically significantly higher than those recorded not only among healthy children of the control group, but also in the group of patients with the articular form of the disease. Among the reasons for the development of endogenous intoxication syndrome, it is necessary to take into account the presence of a current, widespread inflammatory-destructive process in the tissues of the microvasculature of the “shock” organs, as well as intoxication associated with the infectious process often suffered on the eve of vasculitis. Conclusion. It is advisable to use the determination of the indicator of molecules of average mass as an additional criterion for the severity of hemorrhagic vasculitis and a prognostic factor for the development of glomerulonephritis.